Hyperbolicity of the canonical genus two knots. (November 2020) - Stoimenow, A.
Abstract: We classify the non-hyperbolic knots (i.e., torus, satellite and composite knots) of canonical genus at most 2. We use cut-and-paste and combinatorial arguments, but most substantially we develop an approach for (computationally) testing knot primeness using link polynomials.